Presence of Candida albicans in Root Canals of Teeth with Apical Periodontitis and Evaluation of their Possible Role in Failure of Endodontic Treatment - Kumar, Jay (J Int Oral Health, 2015)
BACKGROUND: Candidal organisms are commensals of the oral cavity and their opportunistic infection depends on the interplay of local and systemic factors. Endodontic treatment failure has been associated with the persistence of microbial flora following therapy in the root canal system, and this includes fungi like Candida, which are resistant to conventional root canal irrigants. MATERIALS AND METHODS: A total of 20 mandibular molars were included in the study of which 15 were primary randomized controlled trial cases, whereas 5 were retreatment cases. The patient’s saliva, as well as the root canal flora, were examined for the presence of Candida organisms and further confirmed for the presence of Candida albicans. RESULTS: Of the 20 samples comprising the study group, the saliva culture revealed 11 of them to have a colony forming unit (CFU) >400 and 9 of the 20 canals microbiology showed CFU >400. Among the 15 first-time root canal treatment cases, saliva examination these revealed 8 of them to have CFU >400 and the canal microbiology of these showed 6 of them to have CFU >400. Among the retreatment cases, 3 of the 5 cases showed CFU >400 in both the saliva DN canal culture. CONCLUSION: Candidal contamination of the root canals could be the cause of endodontic treatment failure and thus emphasizes the importance of rubber dam isolation and the use of irrigants with antifungal properties for sufficient duration during treatment.